ANALISIS KELELAHAN KERJA TERHADAP FAKTOR UMUR, MASA KERJA, BEBAN KERJA DAN INDEKS MASA TUBUH PADA DOSEN REGULER FAKULTAS TEKNIK, UNIVERSITAS TEKNOLOGI SUMBAWA TAHUN 2019 - Silvia Firda Utami; Indria Kusumadewi; Ryan Suarantalla (Hexagon Jurnal Teknik dan Sains, 2020)
Fatigue in lecturers can have an impact on reducing work productivity and decreasing work concentration. The purpose of this study was to determine the feeling of work fatigue experienced by Regular Lecturers in the Faculty of Engineering-Sumbawa University of Technology and to determine the relationship of perception of work fatigue based on the factors causing work fatigue in the Regular Lecturers in the Faculty of Engineering-Sumbawa University of Technology. From these objectives this study looks at the relationship between the variables Dependent (Age, Working Period, Workload and Body Mass Index) with Independent variables (Work Fatigue). The method used is quantitative, namely using a statistical test that is Chi-Square with data analysis using two, namely Univariate and Bivariate. The sampling technique uses Exhausive Sampling with 39 respondents. Then the data collection of work fatigue uses the Work Fatigue Measurement Questionnaire (KAUPK2). The results of this study are 27 Regular Lecturers feel work fatigue with the category of thirsty throat. The perception of fatigue is still below 50%, so it can be concluded that there is no perception of fatigue experienced by regular lecturers in the Faculty of Engineering, Universitity Technology of Sumbawa. Then, from the four dependent factors that were tested with independent factors, the results were work period, body mass index and work load that had a relationship with work fatigue in the regular lecturer at the Faculty of Engineering, University Technology of Sumbawa.